Malaria mosquitoes use leg push‐off forces to control body pitch during take‐off - van Veen, Wouter G. (J Exp Zool A Ecol Integr Physiol, 2019)
Escaping from a blood host with freshly acquired nutrition for her eggs is one of the most critical actions in the life of a female malaria mosquito. During this take‐off, she has to carry a large payload, up to three times her body weight, while avoiding tactile detection by the host. What separates the malaria mosquito from most other insects is that the mosquito pushes off gently with its legs while producing aerodynamic forces with its wings. Apart from generating the required forces, the malaria mosquito has to produce the correct torques to pitch‐up during take‐off. Furthermore, the fed mosquito has to alter the direction of its aerodynamic force vector to compensate for the higher body pitch angle due to its heavier abdomen. Whether the mosquito generates these torques and redirection of the forces with its wings or legs remains unknown. By combining rigid‐body inverse dynamics analyses with computational fluid dynamics simulations, we show that mosquitoes use leg push‐off to control pitch torques and that the adaption of the aerodynamic force direction is synchronized with modulations in force magnitude. These results suggest that during the push‐off phase of a take‐off, mosquitoes use their flight apparatus primarily as a motor system and they use leg push‐off forces for control.